2013
DOI: 10.1073/pnas.1221194110
|View full text |Cite
|
Sign up to set email alerts
|

Flavodiiron proteins Flv1 and Flv3 enable cyanobacterial growth and photosynthesis under fluctuating light

Abstract: Cyanobacterial flavodiiron proteins (FDPs; A-type flavoprotein, Flv) comprise, besides the β-lactamase–like and flavodoxin domains typical for all FDPs, an extra NAD(P)H:flavin oxidoreductase module and thus differ from FDPs in other Bacteria and Archaea. Synechocystis sp. PCC 6803 has four genes encoding the FDPs. Flv1 and Flv3 function as an NAD(P)H:oxygen oxidoreductase, donating electrons directly to O 2 without production of reactive oxygen species. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
313
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 304 publications
(334 citation statements)
references
References 13 publications
20
313
0
1
Order By: Relevance
“…This might be due to a differential effect on intron splicing depending on the location of the insertion in the intron. Similar patterns of accumulation were previously observed for the Flv1 protein in the Synechocystis flv3 mutant (Allahverdiyeva et al, 2013) and for the FlvA protein in the P. patens flvb mutant (Gerotto et al, 2016), which were interpreted by the existence of a functional heterodimer between Flv1 and Flv3 in Synechocystis and between FlvA and FlvB in P. patens.…”
Section: Identification and Preliminary Characterization Of Four Indesupporting
confidence: 84%
See 2 more Smart Citations
“…This might be due to a differential effect on intron splicing depending on the location of the insertion in the intron. Similar patterns of accumulation were previously observed for the Flv1 protein in the Synechocystis flv3 mutant (Allahverdiyeva et al, 2013) and for the FlvA protein in the P. patens flvb mutant (Gerotto et al, 2016), which were interpreted by the existence of a functional heterodimer between Flv1 and Flv3 in Synechocystis and between FlvA and FlvB in P. patens.…”
Section: Identification and Preliminary Characterization Of Four Indesupporting
confidence: 84%
“…The physiological function of the different O 2 photoreduction pathways has been controversial, since they have been alternatively viewed as futile pathways resulting in a waste of energy, as protective mechanisms avoiding photooxidative damage, or as a mean to (re)-equilibrate the balance between reducing and phosphorylating powers through pseudocyclic photophosphorylations (Badger, 1985;Allen, 2003). In cyanobacteria, flavodiiron proteins catalyze NADPH-dependent reduction of O 2 at the PSI acceptor side (Vicente et al, 2002;Helman et al, 2003;Allahverdiyeva et al, 2013). The Synechocystis sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By consequence, no intermediary ROS compounds are formed in cyanobacteria (Allahverdiyeva et al 2013(Allahverdiyeva et al , 2015. With no ROS compounds formed, the hypothesis was put up that for cyanobacteria the need to handle the ROS compounds superoxide and HP is less compulsory than in green algae, and hence that cyanobacteria are likely more sensitive to HP than eukaryotic algae.…”
Section: Mode Of Action Of Hydrogen Peroxidementioning
confidence: 99%
“…Flavodiiron proteins (FDPs), originally called A-type flavoproteins or Flvs (Wasserfallen et al, 1998), were recently demonstrated to have an important role in photoprotection of the photosynthetic machinery (Zhang et al, 2009Allahverdiyeva et al, 2011Allahverdiyeva et al, , 2013Ermakova et al, 2013). FDPs in general are most widespread among strict and facultative anaerobic bacteria.…”
mentioning
confidence: 99%